Epidemiology, etiology and complications of falls in patients treated at the Geriatric Ward - Otremba, Iwona (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Introduction. Falls are a major geriatric problems. They are the cause of reduced quality of life and disability. The aim of this study was to evaluate the frequency, causes of falls, the nature of injuries associated with them and the possibility of increasing the safety of patients in geriatric wards. Material and methods. The study included 100 consecutive patients of Geriatric Ward an average age of 78.0 ± 7.72 years (mean ± SD). The questionnaire prepared by the authors, containing 14 questions regarding any failures and their causes. Cognitive functions was assessed by the MMSE (Mini-Mental State Examination), independence by ADL scale (Activities of Daily Living), the risk of falls by the scale Berg (Berg Balance Scale). Results. Isolated moved 36% of patients, with the assistance of 22%. Orthopedic appliances used the 31%. On the trolley it passed 3% of patients, 8% remained in bed. On a scale Berg 37% of 21–40 points, 18% received 0–20 points. By ADL 7% were 3–4 points, 12% — ≤ 2 points. The MMSE 19% received 19–23 points, 10% were 11–18 points, 6% were ≤ 10 points. 6% of respondents had used ≥ 10 drugs, 66% — ≥ 4 drugs. At 66% in the last year had at least one fall. 75% suffered injury. For fractures occurred in 25%. The most common site was the home of the fall (51%). The most common cause internal collapse were dizziness (48%), external (46%) and uneven surfaces. The fall during hospitalization occurred in 7%. None of the patients there were no injuries. The reason for the fall in 3% were dizziness in 2% of inappropriate footwear, in 1% hypotension. Conclusions. Fall risk assessment and prevention should be a regular part of the functioning of geriatric ward.